Partial Pulpotomy with Mineral Trioxide Aggregate in Permanent Incisors with Complicated Crown Fracture: 5-Year Follow-Up. (7th September 2020) - Gomes, Isabel
Abstract : Traumatic dental injuries are highly prevalent among children. This article describes a case report of a patient who has experienced dental trauma at 8 years old, which has led to enamel-dentine fracture with pulp exposure in the left central incisor and crown-root fracture with pulp exposure in the right central incisor. Partial pulpotomy was performed with the aim of maintaining the neurovascular bundle, thus allowing normal radicular formation. During follow-up 5 years later, teeth were asymptomatic and with no evidence of radiolucent lesions in radiographic examinations. This report demonstrates that traumatic fractures with pulp exposure can be treated effectively by the described technique.